2020
DOI: 10.1021/acssuschemeng.0c03141
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of WO3 Films with Controllable Crystallinity for Improved Near-Infrared Electrochromic Performances

Abstract: In this study, a WO 3 film with controllable crystallinity has been prepared by radio frequency magnetron sputtering. The WO 3 film with about 400 nm thickness and controllable crystallinity not only has the advantages of amorphous WO 3 with large transmittance modulation and short switching response time but also has the outstanding cyclic stability of crystalline WO 3 . Therefore, this WO 3 film exhibits superior electrochromic performances including large transmittance modulation in the near infrared regime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(38 citation statements)
references
References 49 publications
0
35
0
Order By: Relevance
“…Furthermore, more active units could effectively participate in the redox reactions and more ions can be stored in the EC layer during the EC process. [ 29,30 ]…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, more active units could effectively participate in the redox reactions and more ions can be stored in the EC layer during the EC process. [ 29,30 ]…”
Section: Resultsmentioning
confidence: 99%
“…In addition to these strategies, the electrochromic properties, cycling life, and structural stability of a bifunctional material (such as WO 3 and NiO) are closely related to its crystalline feature and crystallinity. 12 In the literature, [13][14][15][16][17][18][19][20] it has been reported that each crystalline feature and oriented crystal face of the electrode material can show a different opticalelectrochemical performance and cycling stability due to different atomic arrangement and surface energy. For example, Kang et al synthesized (001)-oriented monoclinic nanorod WO 3 films on FTO by a seed-assisted solvothermal and thermal treatment process.…”
Section: Introductionmentioning
confidence: 99%
“…8,67 Other recent approaches attempted based on energy savings EC materials and technologies for novel multifunction are published elsewhere. 67,68,[70][71][72][73][74][75][76][77][78] Modern commercial buildings in European countries have installed EC smart windows functioning instead of the active air conditioning, and approximately 4.5% of energy can be saved annually in the USA and Australia. 79 Similarly, the auto-dimming smart glass and automotive rear-view mirrors have been commercialized.…”
Section: Introductionmentioning
confidence: 99%